Postnational musical identities : cultural production, distribution, and consumption in a globalized scenario - Corona, Ignacio, 1960-; Madrid, Alejandro L. (Lexington Books, 2008)
"Postnational Musical Identities gathers interdisciplinary essays that explore how music audiences and markets are imagined in a globalized scenario, how music reflects upon new understandings of citizenship beyond the nation-state, and how music works as a site of resistance against globalization."--Jacket.